Posttraumatic, dissociative and grief symptoms in Turkish children exposed to the 1999 earthquakes - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Grief and dissociation after traumatic exposures are among the most important predictors of posttraumatic stress disorder (PTSD). This article introduces the Traumatic Dissociation and Grief Scale (TDGS), a 23-item measure easily administered. The TDGS, the Child PTSD-Reaction Index (CPTSD-RI), and a questionnaire concerning risk factors related to the event (losses, injury, and witnessing death and injuries) were administered to school-aged children who had been directly exposed to the 1999 earthquakes in Turkey and to a nonexposed control group. Factor analysis of the TDGS yielded four factors: perceptual distortions, body-self distortions, irritability, and guilt and anhedonia. A moderate positive correlation was noted between the TDGS and the CPTSD-RI. Different sets of risk factors were associated with the different scale factors. The results suggest that the assessment of psychopathology in children following a disaster requires the complementary evaluation of symptoms of posttrauma, dissociation, and grief.
Keywords: STRESS-DISORDER; SNIPER ATTACK; DISASTER; AGE; DIAGNOSIS; RESPONSES; TRAUMA; SCALE